Evidence of bacteriophage-mediated horizontal transfer of bacterial 16S rRNA genes in the viral metagenome of the marine sponge Hymeniacidon perlevis - Harrington, C.; Del Casale, A.; Kennedy, J.; Neve, H.; Picton, B.; Mooij, M.; O'Gara, Fergal; Kulakov, L.; Larkin, M.; Dobson, A. (Society for General Microbiology, 2012)
Marine sponges have never been directly examined with respect to the presence of viruses or their potential involvement in horizontal gene transfer. Here we demonstrate for the first time, to our knowledge, the presence of viruses in the marine sponge Hymeniacidon perlevis. Moreover, bacterial 16S rDNA was detected in DNA isolated from these viruses, indicating that phage-derived transduction appears to occur in H. perlevis. Phylogenetic analysis revealed that bacterial 16S rDNA isolated from sponge-derived viral and total DNA differed significantly, indicating that not all species are equally involved in transduction.